THE REPRESENTATION OF FEMALE CHARACTER IN EDGE OF TOMORROW (2014) FILM BASED ON FEMINIST FILM CRITICS - Prismanisa, Lana (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2021)
(Title: The Representation of Female Character in